Incorporating Specific Functional Strength Integration Techniques to Improve Functional Performance for Veterans After Total Hip Arthroplasty: Protocol for a Randomized Clinical Trial. Issue 11 (8th August 2019) - Judd, Dana L; Cheuy, Victor A; Forster, Jeri E; Christiansen, Cory L; Stevens-Lapsley, Jennifer E
Abstract: Background: Total hip arthroplasty (THA) is a common procedure, yet persistent deficits in functional performance exist after surgery. These deficits may be related to movement compensations observed after THA, which negatively affect quality of life and may increase morbidity and health care utilization, including in the veteran population. However, the best rehabilitative approach to remediating movement compensations and physical function deficits has not been determined. Objective: The objective is to determine if a functional strength integration intervention (FSI), as part of a post-THA rehabilitation program, improves movement compensation, physical function, muscle strength, and self-reported outcome measures more than a control group (CON) undergoing a standard of care exercise program. Design: This is a 2-arm randomized, controlled clinical trial. Setting: The Veteran Affairs outpatient physical therapy clinics and academic research laboratory will be the settings. Participants: One hundred veterans undergoing THA for hip osteoarthritis will be included in the study. Interventions: Participants will be randomized to either the FSI or CON group and participate in visits of physical therapy over 8 weeks. The FSI protocol will include targeted exercise to improve muscular control and stability around the hip and trunk to minimize movement compensation during daily activity combined with progressive resistance exercise. The CON protocol will include patient education, flexibility activity, and low load resistance exercise. Measurements: Functional performance, muscle strength and endurance, and self-reported outcomes will be measured at baseline (prior to surgery), midway through intervention (6 weeks after surgery), at the end of intervention (10 weeks after surgery), and 26 weeks after THA. Limitations: The inability to blind treating therapists to study arm allocation is a limitation. Conclusions: The proposed study aims to determine if targeted FSI can affect movement compensation to improve functional outcomes after THA more than traditional rehabilitation paradigms.